2016
DOI: 10.1101/090175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrotransposon Activation Contributes to Neurodegeneration in aDrosophilaTDP-43 Model of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are two incurable neurodegenerative disorders that exist on a symptomological spectrum and share both genetic underpinnings and pathophysiological hallmarks. Functional abnormality of TAR DNA-binding protein 43 , an aggregation-prone RNA and DNA binding protein, is observed in the vast majority of both familial and sporadic ALS cases and in~40% of FTLD cases, but the cascade of events leading to cell death are not understood. We h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 119 publications
1
7
1
Order By: Relevance
“…Retrotransposons, a subset of transposable elements (TEs), are genomic parasites capable of inserting new copies of themselves throughout the genome by a process called retrotransposition. Previous work from our lab and others has shown that TDP-43 represses retrotransposon transcripts at the RNA level in animal models of TDP-43 pathology (Krug et al, 2017;Li et al, 2012). However, a role for TDP-43 in general retrotransposon silencing has not been demonstrated, nor whether TDP-43 pathology in ALS patients correlates with retrotransposon de-silencing.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Retrotransposons, a subset of transposable elements (TEs), are genomic parasites capable of inserting new copies of themselves throughout the genome by a process called retrotransposition. Previous work from our lab and others has shown that TDP-43 represses retrotransposon transcripts at the RNA level in animal models of TDP-43 pathology (Krug et al, 2017;Li et al, 2012). However, a role for TDP-43 in general retrotransposon silencing has not been demonstrated, nor whether TDP-43 pathology in ALS patients correlates with retrotransposon de-silencing.…”
Section: Introductionmentioning
confidence: 81%
“…TDP-43 has known roles in RNA splicing, stability, and small RNA biogenesis (Cohen et al, 2011). Recently, several studies have suggested that TDP-43 also plays a role in regulating the activity of retrotransposons (Chang and Dubnau, 2019;Krug et al, 2017;Li et al, 2015;Saldi et al, 2014). Retrotransposons, a subset of transposable elements (TEs), are genomic parasites capable of inserting new copies of themselves throughout the genome by a process called retrotransposition.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear how much, if at all, the 3 0 L1-genome junction depletion observed recently in WGS and RC-seq data [31] affected the false negative rate calculation of this study, given that the WGS analysis appeared to group all TE families together when calculating false negative rate, and the 3 0 depletion observed elsewhere was L1-specific [31]. More generally, it is unknown how much L1 activity varies in the brains of different species, or different inbred animal strains, or for that matter how much ageing and senescence impact on TE mosaicism in species with very dissimilar lifespans [123][124][125][126]. It is nonetheless remarkable that L1 mosaicism may be very common in the mouse brain, and conserved in Mammalia, based on the conservative estimate that olfactory neurons contain at least one somatic L1 insertion, on average [116].…”
Section: Box 2 Engineered L1 Mobilization In Neural Progenitor Cellsmentioning
confidence: 97%
“…Moreover, knockdown of TDP‐43 increases sensitivity to α‐amanitin, a transcription‐arresting agent (Hill et al , ). In support of a link between TDP‐43 pathology and genomic instability, overexpression of human TDP‐43 (hTDP‐43) in a fly model resulted in nuclear clearance of the protein, derepression of retrotransposable elements, and cell death from increased DNA damage (Krug et al , ). The molecular details concerning how TDP‐43 contributes to the prevention or repair of transcription‐associated or other forms of DNA remain to be further investigated.…”
Section: Dna Damagementioning
confidence: 99%